2. The Effect Of Sipatah-patah (Cissus quadrangularis Salisb) Extract On The Femur Bone Density of White Rat (Rattus norvegicus) with Model Ovariectomy - Mustafa Sabri; Debby Novita ayumi; Muhammad Jalaluddin; Hamny Hamny; Cut Dahlia Iskandar; Herrialfian Herrialfian (Jurnal Medika Veterinaria, 2019)
This research aimed to determine the effect of giving Sipatah-patah extract toward the histopathological and femur bone growth of white rat that was ovariectomized. The experimental animals that were used were 12 white rats divided into 4 treatment group with 3 repetitions. K0 was the ovariectomized rat without giving Sipatah-patah extract (ESP); K1, K2 and K3 were ovariectomized rats which were given Sipatah-patah extract with multilevel doses of 500 mg/kg BW, 700 mg/kg BW and 900 mg/kg BW for 30 days. On the 31st day, rats were euthanized using chloroform and os femur that was taken to being made into histological preparation.  There was the decrease in the bones density of the K0 group which is characterized by thinning of trabecular structure, there were lots of osteoclast cells on the edge of the trabecular and lower density of active osteoblasts and passive osteoblasts. The rat of group K1 and K2 showed an improvement on the trabecular structure and lower osteoclast than group K0. The rat of group K3 had a visible improvement of the most congested trabecular structures, cohesive with the most density cell of active osteoblasts than the other groups. The result of this research concluded that the giving of Sipatah-patah extract doses 900 mg/kg BW showed a higher density of trabecular and active osteoblasts than the control group, K1 and K2 on the white rat bones that were ovariectomized.